Examining religious commitment, personality, and well-being among Latter-day Saints. Issue 3 (3rd July 2019) - Allen, G. E. Kawika; Hafoka, Ofa; Fischer, Lane
ABSTRACT: This study examined religious commitment, the big five personality traits, social interaction anxiety, and anger among 110 members of The Church of Jesus Christ of Latter-day Saints (LDS). Results suggest the majority of the participants are religious, score high on agreeableness and conscientiousness, and low on social interaction anxiety and anger. Agreeableness mediated the relationship between religious commitment and anger, and extraversion moderated the relationship between religious commitment and social interaction anxiety. Counseling strategies are discussed for social work providers. Implications and future directions are discussed.